A Creative Combination of SCRUM and Market Research with a Social Approach (National Administration Journal, 2025)
This research analyzes the integration of the agile SCRUM methodology with market research from a social perspective, applied within a university context. The study arises from the need to design learning experiences that transcend theoretical knowledge and actively connect students with real community issues. A mixed methodological approach was adopted, combining data collection techniques with collaborative dynamics inherent to SCRUM, thereby structuring high-performance academic teams for the development of socially relevant projects. The results reveal that the implementation of SCRUM in market research processes enhances student motivation, organization, and creativity, fostering active and situated learning. Furthermore, a positive impact was observed in the beneficiary communities, as the proposed solutions incorporated principles of social responsibility and sustainability. Key findings highlight improvements in critical thinking, the strengthening of soft skills such as leadership and communication, and the consolidation of an ethical vision of marketing. It is concluded that the articulation of SCRUM and market research constitutes an innovative pedagogical strategy that promotes students’ comprehensive development while simultaneously providing responses to concrete social challenges. This study contributes empirical evidence for the redesign of teaching-learning methodologies in the fields of economics and business administration, aiming to advance a higher education model more strongly committed to its social environment.
Keywords: SCRUM